2001
DOI: 10.1074/jbc.m107176200
|View full text |Cite
|
Sign up to set email alerts
|

Autoinhibition of Mixed Lineage Kinase 3 through Its Src Homology 3 Domain

Abstract: Mixed lineage kinase 3 (MLK3) is a serine/threonine protein kinase that functions as a mitogen-activated protein kinase kinase kinase to activate the c-Jun NH 2 -terminal kinase pathway. MLK3 has also been implicated as an IB kinase kinase in the activation of NF-B. Amino-terminal to its catalytic domain, MLK3 contains a Src homology 3 (SH3) domain. SH3 domains harbor three highly conserved aromatic amino acids that are important for ligand binding. In this study, we mutated one of these corresponding residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
74
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 41 publications
(43 reference statements)
2
74
0
Order By: Relevance
“…The binding of the active, small GTPase disrupts this autoinhibitory conformation, resulting in autophosphorylation of the activation loop and activation of PAK (53, 54). Our lab has previously reported that MLK3 is autoinhibited through association of its N-terminal SH3 domain with a sequence containing Pro 469 , which, based at least on primary sequence, is situated in close proximity between the zipper domain (amino acids 400 -462) and the CRIB motif (amino acids 498 -514) (19). Thus although they utilize different structural domains/elements, PAK and MLK3 appear to share a common theme of GTPasemediated disruption of autoinhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of the active, small GTPase disrupts this autoinhibitory conformation, resulting in autophosphorylation of the activation loop and activation of PAK (53, 54). Our lab has previously reported that MLK3 is autoinhibited through association of its N-terminal SH3 domain with a sequence containing Pro 469 , which, based at least on primary sequence, is situated in close proximity between the zipper domain (amino acids 400 -462) and the CRIB motif (amino acids 498 -514) (19). Thus although they utilize different structural domains/elements, PAK and MLK3 appear to share a common theme of GTPasemediated disruption of autoinhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Zipper-mediated homo-oligomerization is required for full activity of MLK3, proper substrate phosphorylation, and activation of the JNK pathway (17,18). Work from our lab indicates that MLK3 is autoinhibited through an interaction between its SH3 domain and a proline-containing sequence within MLK3 (19).…”
mentioning
confidence: 99%
“…8 The SH3 domain of MLK3 can bind a proline residue in a region between the leucine zipper and the CRIB motif resulting in autoinhibition. 9 Overexpression of Cdc42 has been shown to induce activation of MLK3 and this activation requires the MLK3 CRIB motif. 7,10 It has been proposed that binding of GTP-bound Rac or Cdc42 to MLK3 through the CRIB motif could disrupt the autoinhibitory interaction and allow MLK3 kinase activation.…”
Section: Introductionmentioning
confidence: 99%
“…A point mutation (Y52A) in the SH3 domain-binding site of MLK3 abolishes binding to the SH3 domain and increases the MLK3 activity (43). The Y52A mutant shows a 2-fold increase in autophosphorylation and a 2.5-fold increase in histone phosphorylation.…”
Section: Discussionmentioning
confidence: 99%